Pengaruh Penyosohan Gabah dan Pemasakan terhadap Kandungan Vitamin B Beras Merah - Indrasari, Siti Dewi (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
The number of improved red rice varieties (red color caryopsis) is still limited, namely Bahbutong and Aek Sibundong. Red rice is useful as functional food due to its antocyanin content which have a potential function as antioxidant. The research was aimed to study the effect of processing (milling and cooking) on the thiamin (vitamin B1), riboflavin (vitamin B2), niacin (vitamin B3), and pyridoxin (vitamin B6) content of new varieties, local red vareties and advanced lines of red rice. The materials used in the experiment were two red rice advanced lines, local red rice (Jembar Beureum and Jatiluwih), red rice improved variety Aek Sibundong, and white rice variety Ciherang. Results showed that milling and cooking processes reduce thiamin, riboflavin, niacin , and pyridoxin contents on advanced improved red lines, red improved variety, local red varieties and Ciherang white improved variety. Jembar Beureum milled and cooked rice had the highest thiamin and niacin content. Jatiluwih milled and cooked rice had the highest riboflavin and pyridoxin content. Local red rice had higher vitamin B content than improved red advanced lines, Aek Sibundong and Ciherang white rice. Local red rice varieties may be used as parent material on the breeding program to develop red rice improved varieties with higher vitamin B content.